Power cable defects and their influence on electric field distribution in polyethylene insulation - Kucheriava, I.M. (Технічна електродинаміка, 2017)
The paper studies the cable degradation mechanisms and electric field distributions in the polyethylene insulation of power cables with typical defects at macroscopic level including crack and numerous air bubbles in the insulation, protrusion of inner semiconducting layer, its air gapping with cable insulation and interruption along the cable conductor, holes in outer semiconducting layer, its delamination from copper shield as well as small air hole in the shield owing to corrosion. The three-dimensional computer modeling and analysis of electric field distributions are carried out in the chosen region of the cable containing the defects. The patterns of the distributions and local field enhancement in the vicinity of the defects are shown. The effect of defects on electric field in the polyethylene cable insulation is revealed. Виконується комп'ютерне моделювання електричного поля в поліетиленовій ізоляції силових кабелів з характерними дефектами на макрорівні – тріщиною та численними повітряними порожнинами в основній ізоляції, виступом напівпровідного шару по жилі, його нещільним приляганням до ізоляції і перериванням вздовж жили, пустотами в зовнішньому напівпровідному шарі, його відшаруванням від мідного екрана, а також повітряним проміжком у мідному екрані, пов'язаним з корозією матеріалу. Тривимірне моделювання та дослідження електричного поля проводяться в об’ємі кабеля, що містить виділену невелику область з дефектами. Показано характер розподілу поля і його посилення в зоні розташування структурних дефектів кабеля та вплив дефектів на розподіл поля в основній ізоляції. Выполняется компьютерное моделирование электрического поля в полиэтиленовой изоляции силовых кабелей с типичными дефектами на макроуровне – трещиной и многочисленными воздушными полостями в основной изоляции, выступом полупроводящего слоя по жиле, его неплотным прилеганием к изоляции и прерыванием вдоль жилы, пустотами во внешнем полупроводящем слое, отслоением его от медного экрана, а также воздушным промежутком в медном экране, связанным с коррозией материала. Трехмерное моделирование и исследование электрического поля проводятся в объеме кабеля, включающем выделенную малую областью с дефектами. Показаны характер распределения поля и его усиление в зоне расположения структурных дефектов кабеля и влияние дефектов на распределение поля в основной изоляции.